2022
DOI: 10.1186/s10086-022-02039-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of jute stick particleboard using citric acid–glycerol mixture as a natural binder

Abstract: The application of citric acid and glycerol as natural binder was investigated for the manufacturing of jute stick particleboard in this study. The effects of citric acid content (0–30 wt%), citric acid and glycerol mixture (ratio of CA–G), and pressing temperatures on the properties of jute stick particleboard were investigated. Citric acid-bonded jute stick particleboard had good mechanical properties and dimensional stability when citric acid concentration was 20 wt% at pressing temperature of 200 °C. By ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Lee et al, 2019). Other researchers have also reported that the pH of CA adhesive without additives is less than 2, which is consistent with this result(Nitu et al, 2022;Sutiawan et al, 2021). The viscosity of CA adhesive without and with starch was 38 and 45 centipoises, respectively.…”
supporting
confidence: 86%
“…Lee et al, 2019). Other researchers have also reported that the pH of CA adhesive without additives is less than 2, which is consistent with this result(Nitu et al, 2022;Sutiawan et al, 2021). The viscosity of CA adhesive without and with starch was 38 and 45 centipoises, respectively.…”
supporting
confidence: 86%
“…4 Photographs of bonding between layers in cross-sections of rubberwood plywood polycondensation of PKS components with glycerol and/ or citric acid, as well as with rubberwood polymers. Citric acid contains three carboxylic groups esterified with the hydroxy groups of glycerol and/or wood polymers to form the ester product, showing the carbonyl ester overlap with the C=O stretching of PKS component, as well as the C=O stretching in the citric acid structure [31]. In addition, the peak around 1635 cm⁻ 1 that corresponded to the citric acid structure was clearly reduced after the binder was cured.…”
Section: The Bonding Characterization Of Plywoodmentioning
confidence: 99%
“…An increase in temperature has the effect of promoting the reaction between glycerol and citric acid, thereby enhancing bond strength. However, the internal bonding drops after hot compression at 220 °C for 8 min (Nitu et al 2022). Zhao et al (2019) also observed that freeze-dried citric acid, prepared from an 80 wt% aqueous solution of citric acid heated at 100 °C for 2 h, exhibits endothermic peaks at 155 and 212 °C, corresponding to its melting point and decomposing temperature.…”
Section: Introductionmentioning
confidence: 96%
“…5-HMF contains two types of functional groups: aldehyde and hydroxyl groups, which can condense with citric acid molecules through ether and ester linkages, respectively (Sun et al 2019;Zhao et al 2019). The utilization of a citric acid and glycerol mixture also demonstrates the potential to serve as a binder in wood composite production, enhancing the water resistance of the boards (Segovia et al 2020;Nitu et al 2022). The binder prepared from an aqueous solution of mixed citric acid and glycerol, heated at 100 °C for 60 min in a hot water bath, showed a remarkable ability to produce jute stick particleboard when subjected to a high pressing temperature in range of 180 to 200 °C.…”
Section: Introductionmentioning
confidence: 99%